The role of microbial exopolymers in determining the fate of oil and chemical dispersants in the ocean. Issue 1 (21st November 2016) - Quigg, Antonietta; Passow, Uta; Chin, Wei‐Chun; Xu, Chen; Doyle, Shawn; Bretherton, Laura; Kamalanathan, Manoj; Williams, Alicia K.; Sylvan, Jason B.; Finkel, Zoe V.; Knap, Anthony H.; Schwehr, Kathleen A.; et al.
Abstract: The production of extracellular polymeric substances (EPS) by planktonic microbes can influence the fate of oil and chemical dispersants in the ocean through emulsification, degradation, dispersion, aggregation, and/or sedimentation. In turn, microbial community structure and function, including the production and character of EPS, is influenced by the concentration and chemical composition of oil and chemical dispersants. For example, the production of marine oil snow and its sedimentation and flocculent accumulation to the seafloor were observed on an expansive scale after the Deepwater Horizon oil spill in the Northern Gulf of Mexico in 2010, but little is known about the underlying control of these processes. Here, we review what we do know about microbially produced EPS, how oil and chemical dispersant can influence the production rate and chemical and physical properties of EPS, and ultimately the fate of oil in the water column. To improve our response to future oil spills, we need a better understanding of the biological and physiochemical controls of EPS production by microbes under a range of environmental conditions, and in this paper, we provide the key knowledge gaps that need to be filled to do so.